Reliability design optimization of vehicle front-end structure for pedestrian lower extremity protection under multiple impact cases. (September 2015) - Lv, Xiaojiang; Gu, Xianguang; He, Liangguo; Zhou, Dayong; Liu, Weiguo
Abstract: Injuries to the lower extremities are one of the major issues in vehicle to pedestrian collisions. To evaluate pedestrian lower extremity protection, the Transport Research Laboratory Pedestrian Legform Impactor (TRL-PLI) test has been conducted according to the specifications in European Union (EU) regulation. At the same time, a Flexible Pedestrian Legform Impactor (Flex-PLI), which has flexible femur and tibia, is examined in European New Car Assessment Program (Euro-NCAP) rating system. To minimize injury risks of pedestrian lower extremity, this paper presents the design optimization of a typical vehicle front-end structure subjected to two different impact cases of TRL-PLI and Flex-PLI. Several approaches involving sampling techniques, surrogate model, multiobjective optimization algorithm and reliability analysis are introduced and applied. Four different basis functions of radial basis function (RBF) surrogate model are adopted for achieving more accurate solutions for structural optimization and reliability analysis. It shows that the accuracy of the basis function is different and the best one is selected for approximate the objective and constraint functions. In order to take into account the effect of design variables uncertainty, the reliability-based design optimization (RBDO) is conducted, and a Monte Carlo Simulation (MCS) is adopted to generate random distributions of the constraint functions for each design. The differences of the different Pareto fronts of the deterministic optimization and RBDO are compared and analyzed in this study. Finally, the reliability-based optimum design result is verified by using test validation. It is shown that the pedestrian lower extremity injury can be substantially improved for meeting product development requirements through the proposed approach. Highlights: A system reliability optimization approach has been developed to design a typical vehicle front-end structure subjected to two different impact cases of TRL-PLI and Flex-PLI. The prediction capability of four different basis functions of RBF model was compared. Physical tests were used to correlate the finite element models and validate the optimization results.